(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
Abstract Aim To study topographic findings in patients with established vernal keratoconjunctivitis (VKC). Materials and methods In a hospital based cross sectional study, 112 eyes of age group 11-22 years with established case of VKC were selected for topography. Result In 112 eyes with VKC; 69.64% (78 eyes) had significant history of eye rubbing. 14.28% (16 eyes) had Kmax values >=47.2D , 85.71%(96 eyes) had Kmax values <47.2D. 19.64%(22 eyes) had I-S Difference >=1.2D ; 80.36%(90 eyes) had I-S Difference <1.2D. Topographical patterns observed included 49.11%(55eyes) with round pattern, 20.54%(23 eyes) with oval shaped, 9.82%(11 eyes) with symmetric bowtie, 6.25%(7 eyes) with asymmetric bow tie with skewing of radial axis, 5.36%(6 eyes) with inferior steepening, 6.25%(7 eyes) with irregular pattern, 0.89%(1 eye) with crab claw pattern. Conclusion High occurrence of keratoconus-like topographic pattern seen in patients of VKC. Topographic analysis should be performed in all cases of VKC.